Earnings dynamics and firm-level shocks - Benjamin Friedrich; Lisa Laun; Costas Meghir; Luigi Pistaferri (Institute for Fiscal Studies (IFS), 2021)
We use matched employer-employee data from Sweden to study the role of the firm in affecting the stochastic properties of wages. Our model accounts for endogenous participation and mobility decisions. We find that firm-specific permanent productivity shocks transmit to individual wages, but the effect is mostly concentrated among the high-skilled workers. For low-skilled the pass-through is similar for temporary and permanent firm-level shocks and the magnitude smaller. The updates to worker-firm specific match effects over the life of a firm-worker relationship are small. Substantial growth in earnings variance over the life cycle for high-skilled workers is driven by firms. In particular, cross-sectional wage variances by age 55 are roughly one-third higher relative to a scenario with no pass-through of firm shocks onto wages.
Keywords: H51; H55; I18; J26; 330; Income process; Wage dynamics; Firm dynamics